WEB E-PROCUREMENT APPLICATION: USING TECHNOLOGY ACCEPTANCE MODEL TO SUPPLIERS USE OF E-PROCUREMENT IN MALAYSIA - Alaweti, Mohamed Fathi; Azizan, Nurdiana A; Faryadi, Qaise F (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper is research aim to extension of the technology acceptance model (TAM)to web E-procurement system. Focusing on suppliers and the E-procurement system impact on their organization performance, this paper has thus examined the factor that is connected with E-procurement system acceptance at suppliers organizations. A qualitative Data collected from 9 corporate suppliers from over 12 organizations helped with the Validation of the factors comprising perceived usefulness, perceived ease of use, suppliers involvement, reliability, security, vendor support and service provider support are identified and their underlying relationships are discussed in the light of the existing literature. Finally Intermediary results from a cluster analysis show differences among respondents that improve our understanding web-based procurement practice.